Mapeamento multitemporal do uso do solo da bacia hidrográfica do rio Alegria no município de Medianeira - PR - Dalla Valle, Andressa (2014)
The Alegria’sWatershedis the main source of the city of Medianeira, which is directly affected by various activities that contribute to the degradation of the same, conducting studies being required to generate data on the dynamics of the basin. With this, the Geoprocessing satellite imagery of high resolution brings agility and efficiency in monitoring the use and land cover, being an important tool for the achievement of several studies. The aim of this study was to produce thematic maps of land use of the basin, with the use of images from Landsat 5, 7 and 8, the years 1993, 2003 and 2014 respectively, provided by NASA and imported into the Spring program of INPE where were classified using the Maximum Likelihood classifier - Maxver - and generated thematic maps, which allowed performing a multitemporal analysis of this period in which the images were captured. Through multitemporal analysis based on the three land use maps generated, the results showed that most part of land use of the Alegria’s Watershed is destined for agriculture, whether in farming or stage without cultivation, and also that much basin has route within the city, hampering the preservation of riparian vegetation in the vicinity of the Alegria beyond his occupation with irregular housing river.It was possible to check the performance of Maxver that generated good results regarding the classification of certain classes, but with a reasonable degree of confusion.